Antiferromagnetic viscosity model for electromotive microscale with second type nonlinear heat frame - Körpınar, Talat; Körpınar, Zeliha (World Scientific Publ Co Pte Ltd, 2023)
In this paper, we construct second type frame affiliated with the nonlinear heat system. This work is an important study to present a spacelike Landau-Lifshitz second type MATHEMATICAL SCRIPT CAPITAL N?Script capital LScript capital H? viscosity model. Then, we introduce antiferromagnetic spacelike Landau-Lifshitz second type MATHEMATICAL SCRIPT CAPITAL N?Script capital LScript capital H? viscosity model electromotive nonlinear heat microscales. Also, we obtain optical magnetic spacelike second type MATHEMATICAL SCRIPT CAPITAL N?Script capital LScript capital H? microscales in Minkowski space. Finally, we design antiferromagnetic viscosity model for optical Landau-Lifshitz second type MATHEMATICAL SCRIPT CAPITAL N?Script capital LScript capital H? optimistic density.
Keywords: Nonlinear Heat Frame; Antiferromagnetic Microscale; Viscosity Model; Electromotive Heat Microscale; Transfer Enhancement; Equations; Flows; Nanofluids; Evolution; Phase